Fontes epigraphici religionum Celticarum antiquarum. I: Provincia Noricum. Fasciculus 1 und 2 Fasc.2: Die epigraphischen Testimonien - Hainzmann, Manfred (2020)
Thoroughly illustrated edition, translation and commentary of all religious Norican inscriptions with a probably Celtic-speaking background, together with an in-depth linguistic and historical discussion of the single numina and an iconographic study in Fasc. 1. Fasc 1: https://e-book.fwf.ac.at/o:1424 Fasc 2: https://e-book.fwf.ac.at/o:1425